Production-Performance Analysis of Composite Shale-Gas Reservoirs by the Boundary-Element Method - Chenfeng Li (SPE Reservoir Evaluation & Engineering, 2019)
A shale-gas reservoir with a multiple-fractured horizontal well (MFHW) is divided into two regions: The inner region is defined as stimulated reservoir volume (SRV), which is interconnected by the fracture network after fracturing, while the outer region is called unstimulated reservoir volume (USRV), which has not been stimulated by fracturing. Considering an arbitrary interface boundary between SRV and USRV, a composite model is presented for MFHWs in shale-gas reservoirs, which is based on multiple flow mechanisms, including adsorption/desorption, viscous flow, diffusive flow, and stress sensitivity of natural fractures. The boundary-element method (BEM) is applied to solve the production of MFHWs in shale-gas reservoirs. The accuracy of this model is validated by comparing its production solution with the result derived from an analytical method and the reservoir simulator. Furthermore, the practicability of this model is validated by matching the production history of the MFHW in a shale-gas reservoir. The result shows that the model in this work is reliable and practicable. The effects of relevant parameters on production curves are analyzed, including Langmuir volume, Langmuir pressure, hydraulic-fracture width, hydraulic-fracture permeability, natural-fracture permeability, matrix permeability, diffusion coefficient, stress-sensitivity coefficient, and the shape of the SRV. The model presented here can be used for production analysis for shale-gas-reservoir development.